A Shift Algorithm for Exact Computation in Sequential Tests with Binary Outcome - failures, A simple shift algorithm is described enabling the exact determination of power functions; analyses, but the number of interim; times, the monitoring; examples, the continuation regions may be specified as desired To give; (CYTEL, exact properties of designs proposed by the program package East; determined, ) are; far, plans with interim analyses are considered where decisions are based on the conditional power (Biometrical journal, 2000)
A simple shift algorithm is described enabling the exact determination of power functions and sample size distributions for a large variety of closed sequential two‐sample designs with a binary outcome variable. The test statistics are assumed to be based on relative frequencies of successes or failures, but the number of interim analyses, the monitoring times, and the continuation regions may be specified as desired. To give examples, exact properties of designs proposed by the program package EaSt (Cytel, 1992) are determined, and plans with interim analyses are considered where decisions are based on the conditional power given the observations obtained so far.